Toner
By reasonably formulating amorphous and crystalline polyester in toner particles and controlling its distribution on the surface of toner particles, the problem of difficulty in taking into account low-temperature fixability and heat resistance storage in the prior art is solved, and the problem of achieving Excellent image quality and stability in low voltage fixing unit.
Patent Information
- Application Number
- CN202010406395.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-14
- Filing Date
- 2020-05-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-05-14
AI Technical Summary
The existing toner is difficult to take into account both the low-temperature fixability and the heat-resistant storage properties, and image defects and fogging problems are prone to occur in the low-pressure fixing unit, especially the adhesion caused by the orientation and cracking of the crystalline resin. and image stripping.
Toner particles containing amorphous polyester and crystalline polyester are used to measure the secondary ion depth distribution of toner particles on the surface of toner particles by time-of-flight secondary ion mass spectrometer TOF-SIMS, and control the proportion of resin components and The structure is that the amount of amorphous polyester in the range of 0≤t≤10nm is greater than that in the range of crystalline polyester, and the amount in the range of 10
Good low-temperature fixability is achieved, while suppressing image peeling during fogging caused by low-charge toner and folding, thereby improving image stability and heat-resistant storage.
Smart Images

Figure BDA0002491450640000121 
Figure BDA0002491450640000122 
Figure BDA0002491450640000131
Abstract
Description
Technical Field
[0001] The present invention relates to a toner used in an image forming method such as electrophotography. Background Art
[0002] In recent years, image forming apparatuses such as copiers and printers have become smaller and more energy-efficient. In view of this, there is an increasing demand for toners having excellent low-temperature fixability to allow fixation at lower temperatures.
[0003] One method for achieving low temperature fixability is to lower the softening temperature of the binder resin in the toner. However, if the binder resin has a low softening temperature, the heat resistant storage property of the toner decreases, and there is a particular problem of so-called blocking in which toner particles fuse together under a high temperature environment.
[0004] One technique known to solve this problem is to use a crystalline resin in a toner. Since a crystalline resin softens rapidly at the melting point of the resin, the softening temperature of the toner can be lowered to near the melting point while maintaining heat storage resistance near the melting point. Therefore, both low-temperature fixability and heat storage resistance can be achieved by using a crystalline resin in a toner.
[0005] Meanwhile, an effective means for reducing the size of the device is to reduce the size of the fixing unit mounted on the main body, for example. Film fixing is preferably used because it makes it easier to simplify the heat source and the device configuration. However, since film fixing generally uses less heat and low pressure, less heat may be transferred to the toner, and the toner is not easily melted. This may result in image defects in which isolated toners on the fixed image due to insufficient melting of the toner cause color transfer when the image is rubbed.
[0006] In order to solve this problem, the melt viscosity of the toner particle surface is important. Specifically, if the melt viscosity near the toner particle surface can be reduced, the above-mentioned image defects can be suppressed because the toner particles will fuse together during fixing to form a network-like structure. Since fixing by means of a network formed by melting of the toner surface is particularly important in a low-pressure fixing unit, one technique is to control the crystalline resin so that it is easy to exist on the toner particle surface.
[0007] However, the molecular chains of crystalline resins have uniform, regular orientation and low resistance, and are therefore prone to charge leakage. Therefore, if the crystalline resin is exposed on the surface of the toner particles, the amount of low-charged toner increases, and the toner that is not charged as expected is developed on the non-image area, causing the problem of fogging.
[0008] In addition, due to the orientation of the crystalline resin as described above, it is brittle and has the property of being easily broken. Therefore, although the low-temperature fixability to friction is improved if the crystalline resin is controlled so as to be localized on the toner particle surface, when the storage document is folded and stored for a long time, image peeling at the fold and cracks in the image are likely.
[0009] Therefore, there is a need for a toner that provides good low temperature fixability while also suppressing fogging and image peeling of folded images due to low charged toners.
[0010] Various proposals have been made in the past to address these problems.
[0011] In the toner particles described in Japanese Patent Application Laid-Open No. 2015-169770, low-temperature fixability and charging stability are improved with a core-shell structure having two shell layers including a layer of a non-crystalline resin as the outermost layer outside a layer of a crystalline resin.
[0012] In the toner particles of Japanese Patent Application Laid-Open No. 2011-149986, low-temperature fixability and heat storage resistance are improved by using a crystalline resin and a non-crystalline resin in the shell layer of the core-shell structure. Summary of the invention
[0013] However, since the invention of Japanese Patent Application Publication No. 2015-169770 has a non-crystalline resin layer, the melt viscosity of the toner particle surface is not sufficiently reduced, and since it uses a crystalline resin, the effect of improving low-temperature fixability against friction cannot be sufficiently obtained.
[0014] Furthermore, since the toner is composed of a crystalline resin and an amorphous resin in a phase-separated state, the crystalline resin is also likely to form domains in the fixed image without being compatible with the amorphous resin. This is likely to reduce the folding strength imparted by the crystalline polyester domain.
[0015] Furthermore, in Japanese Patent Application Laid-Open No. 2011-149986, it was found that fogging is likely because a large amount of crystalline resin is exposed in the shell layer.
[0016] Furthermore, it was found that if the crystalline resin ratio in the shell layer was reduced to improve the charging characteristics, the low-temperature fixing property was reduced, and it was difficult to achieve both the low-temperature fixing property and the charging performance.
[0017] The present invention provides a toner that can obtain good low-temperature fixability while also suppressing fogging caused by a low-charged toner and image peeling during folding.
[0018] A toner comprising toner particles containing a resin component, wherein
[0019] the resin component contains an amorphous polyester and a crystalline polyester, and
[0020] in the measurement of the depth profile of secondary ions on the surface of the toner particles by time-of-flight secondary ion mass spectrometry (TOF-SIMS), assuming Ia(t) as the intensity of secondary ions derived from the amorphous polyester at a depth of t (nm) from the surface of the toner particles, Ic(t) as the intensity of secondary ions derived from the crystalline polyester at a depth of t (nm) from the surface of the toner particles, and I(t) as the total detected intensity of secondary ions derived from the resin contained in the toner particles at a depth of t (nm) from the surface of the toner particles, the following formulas (1) and (2) are satisfied in the range of 0 ≤ t ≤ 10:
[0021] Ia(t) > Ic(t) > 0.0000 (1)
[0022] (Ia(t) + Ic(t)) / I(t) ≥ 0.80 (2)
[0023] and in the range of 10 < t ≤ 30, there is only one intersection point between the depth profile curve of Ia(t) and the depth profile curve of Ic(t).
[0024] The present invention can provide a toner that can achieve good low-temperature fixability and at the same time suppress fogging caused by low-charged toner and image peeling during folding.
[0025] Further features of the present invention will become apparent from the description of the following exemplary embodiments. Detailed Description
[0026] Unless otherwise specified, descriptions of numerical ranges such as "from XX to YY" or "XX to YY" include the numerical values of the upper and lower limits of the range.
[0027] As described above, a core-shell type toner in which an amorphous resin layer is coated on a core particle containing a crystalline resin as disclosed in Japanese Patent Application Laid-Open No. 2015-169770 is effective in improving the charging characteristics of the toner. However, this is not sufficient to achieve both low-temperature fixability and charging characteristics unless the thickness of the amorphous resin layer and its relationship with the crystalline resin can be precisely controlled. In particular, image defects caused by insufficient toner melting are significant in a low-pressure fixing unit configuration such as film fixing.
[0028] The present inventors have conducted in-depth research on a toner structure that can provide excellent low-temperature fixability, strong charging characteristics, and at the same time prevent image peeling of the fixed image during folding.
[0029] The inventors' study using toner melting simulation showed that the presence of a crystalline resin in a region up to a depth of about 60 nm from the surface of the toner particles is important for melting near the surface of the toner particles. As a result, in a low-pressure fixing unit configuration such as film fixing, adding a crystalline resin to the toner particles to reduce the melt viscosity up to a depth of about 60 nm from the surface of the toner particles is effective for achieving excellent low-temperature fixing properties.
[0030] However, when a large amount of crystalline resin is exposed on the surface of the toner particles, fogging may occur due to insufficient charging. Therefore, in order to achieve both low-temperature fixability and charging characteristics, it is necessary to arrange a sufficient amount of crystalline resin in a region up to a depth of about 60 nm from the surface of the toner particles, while also precisely controlling the structure of the non-crystalline resin having excellent charging characteristics, thereby preventing the crystalline resin from being exposed on the surface of the toner particles.
[0031] Therefore, the present inventors focused on crystalline polyester and non-crystalline polyester as crystalline resins and non-crystalline resins, respectively. The physical properties of polyester resins can be easily controlled by means of their monomer composition, and using polyester resins for both crystalline resins and non-crystalline resins makes it easier to control their structures and compatibility.
[0032] The present inventors have found that the above problems can be solved by the following toner.
[0033] That is, this is a toner having toner particles containing a resin component, wherein
[0034] The resin component contains a non-crystalline polyester and a crystalline polyester, and
[0035] In the depth distribution measurement of secondary ions on the surface of the colorant particle by a time-of-flight secondary ion mass spectrometer TOF-SIMS, assuming that Ia(t) is the intensity of secondary ions originating from the non-crystalline polyester in the colorant particle at a depth of t (nm) from the surface of the colorant particle, Ic(t) is the intensity of secondary ions originating from the crystalline polyester in the colorant particle at a depth of t (nm) from the surface of the colorant particle, and I(t) is the total detected intensity of secondary ions originating from the resin contained in the toner particle at a depth of t (nm) from the surface of the colorant particle,
[0036] Then the following equations (1) and (2) are satisfied in the range of 0≤t≤10:
[0037] Ia(t)>Ic(t)>0.0000 (1)
[0038] (Ia(t) + Ic(t)) / I(t) ≥ 0.80 (2)
[0039] And in the range of 10 < t ≤ 30, there is only one intersection point between the depth distribution curve of Ia(t) and the depth distribution curve of Ic(t).
[0040] The present invention will be described in detail below.
[0041] The above formula (1) shows that the toner particles have both amorphous polyester and crystalline polyester in the region from the surface of the toner particles up to a depth of 10 nm. It also shows that the amount of amorphous polyester in this region is greater than the amount of crystalline polyester.
[0042] The above formula (2) shows that in the region from the surface of the toner particles up to a depth of 10 nm, the amorphous polyester and the crystalline polyester together constitute more than 80% of the resin component.
[0043] That is, by controlling the toner so that the above formula (1) and (2) are satisfied simultaneously in the above region, the crystalline polyester can be arranged near the surface of the toner particles effective for low-temperature fixing, and at the same time, the amount of the crystalline polyester exposed on the surface of the toner particles can be minimized. As a result, good charging characteristics can be achieved.
[0044] In the range of 0 ≤ t ≤ 10, Ia(t) - Ic(t) is preferably from 0.0050 to 0.0350, or more preferably from 0.0050 to 0.0300.
[0045] In the range of 0 ≤ t ≤ 10, (Ia(t) + Ic(t)) / I(t) is preferably 0.85 or more, or more preferably 0.88 or more. There is no particular limitation on the upper limit, but it is preferably 0.99 or less, or more preferably 0.95 or less.
[0046] In the range of 0 ≤ t ≤ 10, Ia(t) can be controlled by controlling the molecular weight and SP value of the amorphous polyester, the SP value difference between the amorphous polyester and the crystalline polyester, and the content of the amorphous polyester in the resin component. Ic(t) can be controlled by controlling the molecular weight and SP value of the crystalline polyester, the SP value difference between the crystalline polyester and the amorphous polyester, and the content of the crystalline polyester in the resin component. (Ia(t) + Ic(t)) / I(t) can be controlled by controlling the SP value, molecular weight, and content of the amorphous polyester and the crystalline polyester.
[0047] The fact that there is only one intersection point between the depth distribution curve of Ia(t) and the depth distribution curve of Ic(t) within the range of 10 < t ≤ 30 indicates the following structure. That is, it indicates that in the region moving from the toner particle surface towards the particle center by more than 10 nm and less than 30 nm, the amounts of the amorphous polyester and the crystalline polyester continuously change. In addition, the amorphous polyester is more abundant at the toner particle surface than at the intersection point, while the crystalline polyester is more abundant inside the toner particle than at the intersection point.
[0048] As described above, a structure having a sufficient amount of crystalline polyester in the region up to a depth of 60 nm from the toner particle surface is necessary for obtaining excellent low-temperature fixability. In the absence of a structure in which the amounts of the amorphous polyester and the crystalline polyester replace each other at an intermediate depth up to 30 nm from the toner particle surface, a sufficient amount of crystalline polyester cannot exist at a depth up to 60 nm from the toner particle surface. If these conditions are not satisfied, excellent low-temperature fixability cannot be obtained due to insufficient toner melting.
[0049] Different from the structure in Japanese Patent Application Laid-Open No. 2015-169770 in which an amorphous resin and a crystalline resin form a phase-separated layer, the toner of the present invention has a structure in which the amounts of the amorphous polyester and the crystalline polyester continuously change from the toner particle surface towards the toner center. As a result, even when only the region closest to the toner surface melts as in the low-pressure fixing unit configuration, the crystalline polyester can instantaneously plasticize the surrounding amorphous polyester and be in a uniformly compatible state.
[0050] When cooling such a molten toner on an image, the crystalline polyester in a uniformly compatible state with the amorphous polyester crystallizes in a state of being finely dispersed without forming large domains. As a result, image peeling of the post-fixed image caused by large domains of the crystalline polyester can be suppressed.
[0051] In order to determine the structure of the toner particles, the present inventors performed secondary ion depth distribution measurement of the toner particles using a time-of-flight secondary ion mass spectrometer TOF-SIMS, which is excellent for analyzing the outermost surface of a substance. Then, the structure of the toner particles was determined based on the obtained secondary ion intensity.
[0052] In TOF-SIMS, the sample surface is irradiated with a high-speed ion beam (primary ion) in a high vacuum, and secondary ions repelled from the sample surface by the sputtering phenomenon are collected so that secondary ions can be stably observed in the region up to about 1 μm from the sample surface.
[0053] Observe the toner particle structure using the depth profiling function of TOF-SIMS. In this process, the area scanned by the primary ion beam is usually an area of one hundred microns square to several hundred microns square, corresponding to an area of several hundred toner particles.
[0054] However, the composition near the surface of the toner particle can be mainly measured, and by etching in the depth direction of the toner particle, the composition of the toner particle can be mainly measured. In particular, in a shallow region, specifically, in the region from the surface of the toner particle up to a depth of 0.5 μm, a high-resolution depth profile can be obtained, and by analyzing the depth profile of the secondary ions corresponding to the constituent components of the toner particle, the structure of the toner particle can be determined.
[0055] In the range of 0 ≤ t ≤ 10, Ia(t) is preferably from 0.0300 to 0.0550, or more preferably from 0.0350 to 0.0500.
[0056] If Ia(t) is 0.0300 or more, the charging performance is sufficient due to the amorphous polyester, and fogging caused by the low-charged toner can be controlled. On the other hand, if it is 0.0550 or less, the amorphous polyester is less likely to hinder the decrease in the melt viscosity on the surface of the toner particle due to the crystalline polyester.
[0057] Ia(30) is preferably from 0.0100 to 0.0250, or more preferably from 0.0150 to 0.0200.
[0058] Ia(60) is preferably from 0.0050 to 0.0100, or more preferably from 0.0050 to 0.0080.
[0059] In the range of 0 ≤ t ≤ 10, I(t) is preferably 0.0500 or more, or more preferably 0.0550 or more. If it is 0.0500 or more, good charging characteristics of the amorphous polyester and good low-temperature fixing properties of the crystalline polyester can be effectively obtained. There is no particular limitation on the upper limit of I(t) in the range of 0 ≤ t ≤ 10, but it is preferably 0.1000 or less, or more preferably 0.0750 or less.
[0060] I(30) is preferably from 0.0500 to 0.0700, or more preferably from 0.0500 to 0.0600.
[0061] I(60) is preferably from 0.0300 to 0.0600, or more preferably from 0.0300 to 0.0400.
[0062] The intersection point between the depth profile curve of Ia(t) and the depth profile curve of Ic(t) must be in the range of 10 < t ≤ 30, or preferably 10 < t ≤ 20.
[0063] If the position of the intersection is greater than 10, good charging characteristics can be obtained due to the non-crystalline polyester present on the surface of the toner particle. If the position of the intersection is 30 or less, good low-temperature fixing properties can be obtained because the structure includes a sufficient amount of crystalline polyester at a depth of up to 60 nm from the surface of the toner particle.
[0064] The position of the intersection point can be controlled by controlling the SP value, molecular weight, and content of the non-crystalline polyester and the crystalline polyester, and the difference in SP value between the non-crystalline polyester and the crystalline polyester.
[0065] As described above, by densely controlling the presence state of the non-crystalline polyester and the crystalline polyester up to a depth of about 60 nm from the toner particle surface, a toner can be provided which can thereby obtain low-temperature fixability and charging characteristics while also highly controlling image peeling during folding.
[0066] <Means of achievement>
[0067] The means for obtaining the above-mentioned specific toner constitution is not particularly limited, but for example, it is preferred to produce toner particles using a non-crystalline polyester and a crystalline polyester having controlled polarity and compatibility in an aqueous medium. Production in an aqueous medium makes it easier to control the polar polyester resin to remain near the surface of the toner particles.
[0068] As an example of a method for producing toner particles, a method for producing toner particles by a suspension polymerization method is described below.
[0069] In the suspension polymerization method, a polymerizable monomer composition is obtained by first uniformly dispersing a non-crystalline polyester resin and a crystalline polyester resin together with a colorant, a polymerization initiator, a crosslinking agent, a charge control agent and other additives as required in a polymerizable monomer for forming a resin component such as a binder resin. Then, a suitable stirring device is used to disperse the obtained polymerizable monomer composition in a continuous phase (e.g., an aqueous phase) containing a dispersion stabilizer to thereby form particles of the polymerizable monomer composition (granulation), and the polymerizable monomer is subjected to a polymerization reaction using a polymerization initiator to obtain toner particles.
[0070] The toner particles are preferably suspension polymerized toner particles.
[0071] Examples of polymerizable monomers include:
[0072] Styrenic monomers, such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-methoxystyrene and p-ethylstyrene;
[0073] Acrylic esters, such as methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, n-propyl acrylate, n-octyl acrylate, dodecyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, 2-chloroethyl acrylate and phenyl acrylate;
[0074] Methacrylates, for example methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, dodecyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, phenyl methacrylate, dimethylaminoethyl methacrylate and diethylaminoethyl methacrylate;
[0075] and acrylonitrile, methacrylonitrile, and acrylamide.
[0076] The polymerizable monomer may be used alone or in combination of two or more.
[0077] Among the above polymerizable monomers, it is preferred to use styrene monomers alone or in combination with other polymerizable monomers such as acrylates or methacrylates. This is because in such a case, the structure of the toner particles is controlled and the low-temperature fixability and charging characteristics of the toner are easily improved.
[0078] Preferably, in particular, a styrene-based monomer and at least one selected from the group consisting of alkyl acrylates and alkyl methacrylates are used as a main component. That is, the resin component preferably contains a styrene acrylic resin.
[0079] Preferably, the polymerization initiator used to produce the toner particles by the suspension polymerization method has a half-life of 0.5 to 30 hours during the polymerization reaction. Preferably, the polymerization initiator is used in an amount of 0.5 to 20 parts by mass relative to 100 parts by mass of the polymerizable monomer. Thus, it becomes possible to obtain a polymer having a maximum molecular weight between 5,000 and 50,000, and to give the toner particles preferred strength and appropriate melting characteristics.
[0080] The peak molecular weight (Mp) of the styrene acrylic resin is preferably 10,000 to 35,000, and more preferably 15,000 to 30,000 from the viewpoints of fixing performance and mechanical strength.
[0081] Examples of the polymerization initiator include:
[0082] Azo or diazo polymerization initiators, such as 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile and azobisisobutyronitrile; and
[0083] Peroxide-based polymerization initiators include benzoyl peroxide, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, lauroyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, di(2-ethylhexyl) peroxydicarbonate, and di(sec-butyl) peroxydicarbonate.
[0084] Among the above, t-butyl peroxypivalate is preferred.
[0085] The polymerization initiator may be used alone or in combination of two or more.
[0086] A crosslinking agent may be used during the production of toner particles according to the suspension polymerization method. The amount of the crosslinking agent is preferably 0.001 parts by mass to 15 parts by mass relative to 100 parts by mass of the polymerizable monomer.
[0087] Examples of the crosslinking agent include compounds having 2 or more polymerizable double bonds, for example, aromatic divinyl compounds such as divinylbenzene and divinylnaphthalene;
[0088] Carboxylates having 2 double bonds, such as ethylene glycol diacrylate, ethylene glycol dimethacrylate and 1,3-butanediol dimethacrylate;
[0089] divinyl compounds such as divinylaniline, divinyl ether, divinyl sulfide and divinyl sulfone; and
[0090] Compounds having 3 or more vinyl groups.
[0091] The cross-linking agent may be used alone or in combination of two or more.
[0092] When the resin component includes a styrene acrylic resin, the content ratio of the styrene acrylic resin in the resin component is preferably 50% by mass to 99% by mass, or more preferably 60% by mass to 95% by mass.
[0093] In addition, when the resin component includes a styrene acrylic resin, in the depth distribution measurement of secondary ions on the surface of the colorant particles by a time-of-flight secondary ion mass spectrometer TOF-SIMS, assuming that Ic(t) is the intensity of secondary ions originating from the crystalline polyester at a depth of t (nm) from the surface of the colorant particles and Is(t) is the intensity of secondary ions originating from the styrene acrylic resin at a depth of t (nm) from the surface of the colorant particles, the following formula (6) is preferably satisfied within the range of 0≤t≤30, and the following formula (6') is more preferably satisfied.
[0094] Ic(t)>Is(t) (6)
[0095] 0.0100 ≤ Ic(t) - Is(t) ≤ 0.0350 (6’)
[0096] Within this range, the melt viscosity on the surface of the toner particles during fixing is sufficiently reduced, and the low-temperature fixability of the toner is improved.
[0097] Within the range of 0 ≤ t ≤ 30, Ic(t) can be controlled by controlling the molecular weight and SP value of the crystalline polyester, the SP value difference between the crystalline polyester and the non-crystalline polyester, and the content of the crystalline polyester in the resin component.
[0098] In addition, in the measurement of the depth distribution of secondary ions on the surface of toner particles by time-of-flight secondary ion mass spectrometry (TOF-SIMS), assuming I(t) as the total detection intensity of secondary ions derived from the resin contained in the toner particles at a depth of t (nm) from the surface of the toner particles and Is(t) as the intensity of secondary ions derived from the styrene-acrylic resin at a depth of t (nm) from the surface of the toner particles, within the range of 30 < t ≤ 60, the following formula (7) is preferably satisfied, and more preferably formula (7’) is satisfied.
[0099] 0.10 ≤ Is(t) / I(t) ≤ 0.50 (7)
[0100] 0.20 ≤ Is(t) / I(t) ≤ 0.45 (7’)
[0101] By satisfying formula (7), the stain resistance is improved.
[0102] Within the range of 30 < t ≤ 60, I(t) can be controlled by controlling the irradiation dose of primary ions in time-of-flight secondary ion mass spectrometry (TOF-SIMS).
[0103] Saturated polyester, unsaturated polyester, or both can be suitably selected as the non-crystalline polyester.
[0104] The ordinary polyester formed from an alcohol component and an acid component can be used as the non-crystalline polyester. Examples of these two components are given below.
[0105] Examples of the alcohol component include ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, cyclohexanedimethanol, butenediol, octenediol, cyclohexenedimethanol, hydrogenated bisphenol A, bisphenols represented by the following formula (A) and their derivatives, and diols represented by the following formula (B), etc.
[0106]
[0107] (In formula (A), R is an ethylene group or a propylene group, x and y are each an integer of 0 or more, and the average value of x+y is 0 to 10.)
[0108]
[0109] (In the formula, R' is -CH 2 CH 2 -、 x' and y' are each an integer greater than 0; and the average value of x'+y' is 0 to 10).
[0110] Examples of trivalent or higher alcohols that can be used to prepare the non-crystalline polyester include sorbitol, 1,2,3,6-hexanetetraol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, trimethylolethane, trimethylolpropane, 1,3,5-trimethylolbenzene, and the like.
[0111] Examples of dicarboxylic acids that can be used to prepare the non-crystalline polyester include dicarboxylic acids and derivatives thereof, such as benzenedicarboxylic acids and anhydrides and lower alkyl esters thereof, including phthalic acid, terephthalic acid, isophthalic acid and phthalic anhydride; alkyl dicarboxylic acids, such as succinic acid, adipic acid, sebacic acid and azelaic acid, and anhydrides and lower alkyl esters thereof; alkenyl succinic acids or alkyl succinic acids, such as n-dodecenyl succinic acid and n-dodecyl succinic acid, and anhydrides and lower alkyl esters thereof; and unsaturated dicarboxylic acids, such as fumaric acid, maleic acid, citraconic acid and itaconic acid, and anhydrides and lower alkyl esters thereof, etc. From the viewpoint of operability and reactivity, benzenedicarboxylic acids such as terephthalic acid or isophthalic acid are desirable.
[0112] Examples of trivalent or higher polycarboxylic acid components that can be used to prepare non-crystalline polyesters include polycarboxylic acids and their derivatives, such as trimellitic acid, pyromellitic acid, 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxy-2-methyl-2-methylenecarboxypropane, tetra(methylenecarboxy)methane, 1,2,7,8-octanetetracarboxylic acid, Empol trimer acid, and anhydrides and lower alkyl esters thereof; and tetracarboxylic acids represented by the following formula (C), etc., and anhydrides and lower alkyl esters thereof.
[0113]
[0114] (In formula (C), X represents an alkylene group or an alkenylene group. However, X is a C having at least one side chain having 3 or more carbon atoms. 5-30 Substituents. )
[0115] Further examples of the alcohol component include polyhydric alcohols such as glycerol, pentaerythritol, sorbitol, sorbitan, and oxyalkylene ethers of novolac type phenolic resins, and examples of the acid component include polycarboxylic acids such as trimellitic acid, pyromellitic acid, 1,2,3,4-butanetetracarboxylic acid, benzophenonetetracarboxylic acid, and anhydrides thereof.
[0116] Any raw material monomers may be used for the crystalline polyester without particular limitation as long as they do not impair crystallinity.
[0117] "Crystallinity" means having a clear endothermic peak (melting point) in differential scanning calorimetry DSC. On the contrary, a resin that does not show a clear endothermic peak is non-crystalline.
[0118] The crystalline polyester may also be a hybrid resin having a polyester moiety and a vinyl moiety. For example, the content of the polyester moiety is preferably 50% by mass to 100% by mass, or more preferably 80% by mass to 100% by mass.
[0119] The crystalline polyester is preferably a polycondensate of monomers including a linear aliphatic dicarboxylic acid and a linear aliphatic diol. The monomers of the aforementioned non-crystalline polyester may also be used as long as the product is crystalline.
[0120] More preferably, the main component of the crystalline polyester is a polyester produced from monomers including a linear aliphatic dicarboxylic acid represented by the following formula (X) and a linear aliphatic diol represented by the following formula (Y). “Main component” means that the content thereof is 50% by mass or more.
[0121] HOOC-(CH 2 ) m -COOH (X)
[0122] [In the formula, m is an integer from 2 to 14.]
[0123] HO-(CH 2 ) n -OH (Y)
[0124] [In the formula, n is an integer from 2 to 16.]
[0125] Since the linear polyester composed of the dicarboxylic acid represented by the above formula (X) and the diol represented by the above formula (Y) has excellent crystallinity, it does not remain compatible with the non-crystalline polyester in the toner and can provide good heat-resistant storage properties.
[0126] When m in formula (X) and n in formula (Y) are 2 or more, low temperature fixability is excellent because the melting point (Tm) is within the desired range for toner fixation. From a practical point of view, if m in formula (X) is 14 or less and n in formula (Y) is 16 or less, it is easier to obtain the material.
[0127] If necessary, a monobasic acid such as acetic acid or benzoic acid or a monohydric alcohol such as cyclohexanol or benzyl alcohol may be used to adjust the acid value or the hydroxyl value.
[0128] The crystalline polyester can be produced by a common polyester synthesis method. For example, the crystalline polyester can be obtained by subjecting a dicarboxylic acid component and a diol component to an esterification reaction or an ester exchange reaction, and then subjecting the dicarboxylic acid component to a polycondensation reaction in a vacuum or in an introduced nitrogen gas by a common method.
[0129] During the esterification or transesterification reaction, a common esterification catalyst or transesterification catalyst such as sulfuric acid, tert-butyl butoxy titanium, dibutyl tin oxide, manganese acetate or magnesium acetate can be used as needed. A commonly known polymerization catalyst such as tert-butyl butoxy titanium, dibutyl tin oxide, tin acetate, zinc acetate, tin disulfide, antimony trioxide or germanium dioxide can also be used for polymerization. The polymerization temperature and the amount of the catalyst are not particularly limited and can be arbitrarily selected as needed.
[0130] A titanium catalyst is preferably used as the catalyst, and a chelate-type titanium catalyst is more preferred. The titanium catalyst has appropriate reactivity, and obtains a polyester having a desired molecular weight distribution.
[0131] The acid value of the crystalline polyester can also be controlled by blocking the terminal carboxyl groups of the polymer. Monocarboxylic acids or monoalcohols can be used for terminal blocking.
[0132] Examples of the monocarboxylic acid include benzoic acid, naphthoic acid, salicylic acid, 4-methylbenzoic acid, 3-methylbenzoic acid, phenoxyacetic acid, bibenzoic acid, acetic acid, propionic acid, butyric acid, caprylic acid, capric acid, lauric acid, stearic acid, and the like.
[0133] Methanol, ethanol, propanol, isopropanol, butanol, or a higher alcohol can be used as the monohydric alcohol.
[0134] Assuming SP1 (cal / cm 3 ) 1 / 2 As the SP value of crystalline polyester and SP2 (cal / cm 3 ) 1 / 2 As the SP value of the non-crystalline polyester, SP2-SP1 is preferably 3.00 to 3.70, or more preferably 3.00 to 3.40.
[0135] As described above, it is preferred to produce the toner particles in an aqueous medium. As a result, if SP2-SP1 is 3.00 to 3.70, the high SP non-crystalline polyester becomes localized so that it covers the toner particle surface, while a part of the crystalline polyester becomes compatible with the non-crystalline polyester. Therefore, both low temperature fixing property and charging characteristics can be achieved.
[0136] If SP2-SP1 is 3.00 or more, the crystalline polyester is less likely to be exposed on the toner particle surface because the non-crystalline polyester is not compatible with the crystalline polyester more than necessary when the toner particles are granulated. As a result, the charging characteristics are appropriate and fogging is suppressed.
[0137] On the other hand, if SP2-SP1 is 3.70 or less, the non-crystalline polyester and the crystalline polyester are in a moderately compatible state. As a result, the crystalline polyester forms domains inside the toner particles, and the amount of the crystalline polyester present in the depth range of about 60 nm from the toner particle surface is appropriate. Thus, the plasticizing effect of the crystalline polyester on the non-crystalline polyester during fixing is improved, resulting in good low-temperature fixing properties.
[0138] The SP value used in the present invention is calculated by the generally used method of Fedors [Poly. Eng. Sci., 14(2), 147(1974)] based on the types and ratios of monomers constituting the resin and the hydrophobic agent.
[0139] The SP value can be controlled by controlling the type and amount of the monomer. For example, a monomer with a high SP value can be used to increase the SP value. On the other hand, a monomer with a low SP value can be used to reduce the SP value. The SP value is expressed in (cal / cm 3 ) 1 / 2 The units are given, but you can also use Formula 1 (cal / cm 3 ) 1 / 2 =2.046×10 3 (J / m 3 ) 1 / 2 Convert to (J / m 3 ) 1 / 2 unit.
[0140] The SP value SP2 of the non-crystalline polyester is preferably 12.40 to 12.90. If it is 12.40 or more, good charging performance can be obtained, and if it is 12.90 or less, good fixing performance can be obtained. SP2 of 12.50 to 12.80 is more preferred.
[0141] The non-crystalline polyester is preferably a polycondensate of a dicarboxylic acid component and a diol component, the diol component containing a bisphenol A alkylene oxide adduct having an average addition mole number of alkylene oxide of 3.0 to 5.0, and the alkylene oxide is preferably selected from ethylene oxide and propylene oxide (more preferably propylene oxide). The average addition mole number is preferably 4.0 to 5.0.
[0142] If the average number of added moles of alkylene oxide is 3.0 or more, more flexible sites are present, the mobility of the main skeleton of the resin increases, and toughness is more easily obtained due to increased viscosity. As a result, when the image is folded after fixing, image peeling (cracks in the image) is easily suppressed even in a severe low-temperature and low-humidity environment.
[0143] On the other hand, if the average added mole number is 5.0 or less, it is easier to suppress the obstruction of fixability due to the high molecular weight.
[0144] In the diol component, the content of the bisphenol A alkylene oxide adduct having an average addition mole number of alkylene oxide of 3.0 to 5.0 is preferably 50 mol % to 100 mol %, or more preferably 80 mol % to 100 mol %.
[0145] The weight average molecular weight (Mw) of the non-crystalline polyester is preferably 7000 to 20000. If Mw is 7000 or more, it is easier to prevent the toner from decreasing in heat storage resistance. If Mw is 20000 or less, fixing hindrance can be suppressed. Mw is more preferably 9000 to 15000.
[0146] The melting point Tm(C) of the crystalline polyester resin is preferably 55 to 90° C., or more preferably 60 to 85° C. If it is 55° C. or higher, the toner has good heat resistant storage property. On the other hand, if the melting point is 90° C. or lower, low temperature fixing property is good.
[0147] The weight average molecular weight Mw of the crystalline polyester is preferably 3000 to 50000. If the weight average molecular weight (Mw) of the crystalline polyester is 3000 or more, the heat storage resistance and the anti-offset property of the toner are improved. If it is 50000 or less, the fixing performance is good. More preferably, Mw is 15000 to 40000.
[0148] The content of the crystalline polyester in the resin component is preferably 5% by mass to 85% by mass, or more preferably 10% by mass to 80% by mass.
[0149] When the resin component includes a styrene acrylic resin, the content of the crystalline polyester is preferably 3 to 20 parts by mass, or more preferably 5 to 20 parts by mass relative to 100 parts by mass of the styrene acrylic resin. If it is 3 parts by mass or more, the aforementioned effects of the present invention are easily obtained. If it is 20 parts by mass or less, the content of the low molecular weight component of the crystalline polyester in the toner is not too high, and the heat resistant storage property is less likely to decrease.
[0150] The content of the non-crystalline polyester in the resin component is preferably 1% by mass to 35% by mass, or more preferably 2% by mass to 30% by mass.
[0151] When the resin component includes a styrene acrylic resin, the content of the non-crystalline polyester is preferably 2 parts by mass to 15 parts by mass, or more preferably 2 parts by mass to 10 parts by mass with respect to 100 parts by mass of the styrene acrylic resin.
[0152] The ratio of the crystalline polyester content to the non-crystalline polyester content (mass ratio: CPES / APES) is preferably 1-10, or more preferably 2-5.
[0153] The acid value of the crystalline polyester is preferably 0.1 mg KOH / g to 5.0 mg KOH / g, or more preferably 0.5 mg KOH / g to 4.0 mg KOH / g. If the acid value is within this range, the crystallinity of the crystalline polyester can be increased, the degradation of the toner during long-term use under a high temperature and high humidity environment can be suppressed, and fogging can be further suppressed. The acid value can be controlled by controlling the composition ratio of the monomers during polymerization.
[0154] The SP value SP1 of the crystalline polyester is preferably 9.45 to 9.80, or more preferably 9.50 to 9.70.
[0155] In the depth distribution measurement of secondary ions on the surface of colorant particles by time-of-flight secondary ion mass spectrometer TOF-SIMS, assuming that Ic(0) is the intensity of secondary ions originating from crystalline polyester at t=0 (i.e., on the outermost surface of the colorant particles), and I(0) is the total detection intensity of secondary ions originating from the resin contained in the colorant particles at t=0, it is preferred to satisfy the following formula (3), and it is more preferred to satisfy the following formula (3').
[0156] 0.10≤Ic(0) / I(0)≤0.40 (3)
[0157] 0.20≤Ic(0) / I(0)≤0.30 (3')
[0158] If the ratio is 0.10 or more, fixing performance and toughness of a fixed image are improved, and if it is 0.40 or less, good charging performance is obtained.
[0159] Ic(0) can be controlled by controlling the molecular weight and SP value of the crystalline polyester, the difference in SP value between the crystalline polyester and the non-crystalline polyester, and the content of the crystalline polyester in the resin component. I(0) can be controlled by controlling the irradiation dose of primary ions in a time-of-flight secondary ion mass spectrometer TOF-SIMS.
[0160] In addition, in the depth distribution measurement of secondary ions on the surface of colorant particles by time-of-flight secondary ion mass spectrometer TOF-SIMS, assuming that Ic(30) is the intensity of secondary ions originating from crystalline polyester at t=30 (i.e., at a depth of 30 (nm) from the surface of the colorant particles), and I(30) is the total detection intensity of secondary ions originating from the resin contained in the colorant particles at t=30, it is preferred to satisfy the following formula (4), and it is more preferred to satisfy the following formula (4').
[0161] 0.40 <Ic(30) / I(30)≤0.90 (4)
[0162] 0.40≤Ic(30) / I(30)≤0.60 (4')
[0163] If the ratio is greater than 0.40, low temperature fixing property is greatly improved because a sufficient amount of crystalline polyester melts instantaneously during fixing even when a low pressure fixing unit such as film fixing is used. If it is less than 0.90, anti-offset property is improved and peeling of the image after fixing can be suppressed.
[0164] Ic(30) can be controlled by controlling the molecular weight and SP value of the crystalline polyester, the difference in SP value between the crystalline polyester and the non-crystalline polyester, and the content of the crystalline polyester in the resin component. I(30) can be controlled by controlling the irradiation dose of primary ions in a time-of-flight secondary ion mass spectrometer TOF-SIMS.
[0165] In depth distribution measurement of secondary ions on the toner particle surface by time-of-flight secondary ion mass spectrometer TOF-SIMS, Ic(t) preferably satisfies the following formula (5) in the range of 0≤t≤10, and more preferably satisfies the following formula (5′).
[0166] 0.0100≤Ic(t)≤0.0350 (5)
[0167] 0.0150≤Ic(t)≤0.0300 (5')
[0168] If Ic(t) is 0.0100 or more, the melt viscosity of the toner particle surface can be effectively reduced by the crystalline polyester, and the image peeling of the image after fixing can be controlled. As a result, the fixing performance and the toughness of the fixed image are improved. If it is 0.0350 or less, the charging performance is improved, and fogging caused by low-charged toner can be suppressed.
[0169] Ic(30) is preferably 0.0150 to 0.0500, or more preferably 0.0200 to 0.0500.
[0170] Ic(60) is preferably 0.0100 to 0.0300, or more preferably 0.0100 to 0.0200.
[0171] The weight average particle diameter D4 of the toner particles is preferably 4.00 μm to 15.00 μm, or more preferably 5.00 μm to 8.00 μm. If the weight average particle diameter (D4) is within this range, good fluidity is obtained because friction charging is easier in the regulating portion to suppress fogging due to low-charged toner, and development can be faithful to the latent image.
[0172] As the toner, any of a magnetic one-component toner, a non-magnetic one-component toner, and a toner used for a non-magnetic two-component developer can be used.
[0173] When a magnetic single-component toner is used as the toner, a magnetic body is preferably used as the colorant.
[0174] Examples of the magnetic body used for the magnetic one-component toner include:
[0175] Magnetic iron oxides, such as magnetite, hematite and ferrite, and magnetic iron oxides including other metal oxides;
[0176] For example, metals such as Fe, Co, Ni, or alloys of these metals with Al, Co, Cu, Pb, Mg, Ni, Sn, Zn, Sb, Be, Bi, Cd, Ca, Mn, Se, Ti, W or V,
[0177] and mixtures thereof.
[0178] Among these magnetic bodies, magnetite is preferred. Examples of the shape of magnetite include polyhedron, octahedron, hexahedron, sphere, needle and scale. Among these shapes, from the perspective of improving image density, a shape with less anisotropy, such as a polyhedron, octahedron, hexahedron or sphere, is preferred.
[0179] The volume average particle size of the magnetic body is preferably 0.10 μm to 0.40 μm. When the volume average particle size is 0.10 μm or more, the magnetic body is less likely to aggregate, and the uniform dispersion of the magnetic body in the toner particles is improved. When the volume average particle size is 0.40 μm or less, the coloring power of the toner is improved.
[0180] The volume average particle size of the magnetic body can be measured using a transmission electron microscope. Specifically, the toner to be observed is fully dispersed in an epoxy resin, and then cured for 2 days at a temperature of 40°C in the atmosphere to obtain a cured product. The obtained cured product is sliced into thin slices using a microtome, and the particle sizes of 100 magnetic bodies are measured in the field of view of the photograph at a magnification of 10,000 to 40,000 times in a transmission electron microscope (TEM). The volume average particle size is then calculated based on the equivalent diameter of the circle equal to the projected area of each magnetic body. Alternatively, an image analysis device can be used to measure the volume average particle size of the magnetic body.
[0181] The content of the magnetic body in the toner particles is preferably 30 parts by mass to 120 parts by mass, and more preferably 40 parts by mass to 110 parts by mass relative to 100 parts by mass of the resin component of the toner particles.
[0182] The magnetic body used in the toner can be produced, for example, according to the following method.
[0183] An aqueous solution containing ferrous hydroxide is prepared by adding a base such as sodium hydroxide in an amount of 1 equivalent or more relative to the iron component to an aqueous solution of a ferrous salt. Air is blown into the prepared aqueous solution while the pH of the aqueous solution is maintained at 7 or more, and then an oxidation reaction of the ferrous hydroxide is carried out while the aqueous solution is heated to 70° C. or more, thereby first forming seed crystals constituting the core of the magnetic body.
[0184] An aqueous solution containing 1 equivalent of ferrous sulfate (based on the amount of the alkali previously added) is added to the slurry solution containing seed crystals. While the pH of the solution is maintained at 5 to 10 and air is blown in, the reaction of ferrous hydroxide is allowed, thus using seed crystals as core to grow magnetic iron oxide particles. The shape and magnetic properties of the magnetic body can be controlled by regulating pH, reaction temperature and stirring conditions. Along with the oxidation reaction, the pH of the solution becomes more and more acidic. However, the pH of the solution should not be less than 5.
[0185] Then, a magnetic body can be obtained by filtering, washing and drying the magnetic iron oxide particles thus obtained.
[0186] In the case of producing the toner according to the polymerization method, the surface of the magnetic body is preferably subjected to a hydrophobic treatment. In the case of surface treatment by a dry method, the surface of the magnetic body which has been washed, filtered and dried may be subjected to a coupling agent treatment.
[0187] In the case of surface treatment by a wet method, once the oxidation reaction is completed, the obtained dry product is thereafter redispersed, or alternatively, the iron oxide obtained by washing and filtering after the oxidation reaction is completed is redispersed in another aqueous medium without drying, and then the coupling treatment can be performed therein.
[0188] In the case of redispersion, specifically, the coupling treatment can be performed by adding a silane coupling agent while stirring the redispersion liquid and raising the temperature after hydrolysis, or alternatively, by adjusting the pH of the redispersion liquid to an alkaline region.
[0189] From the viewpoint of performing uniform surface treatment, among the foregoing, it is preferred to perform filtration and washing once the oxidation reaction is completed, and thereafter, reslurry the product as it is without drying, and then perform surface treatment.
[0190] When the surface treatment of the magnetic body is wet, that is, treated with a coupling agent in an aqueous medium, the magnetic body is first dispersed in an aqueous medium to a primary particle size, and then stirred using a stirring blade to prevent sedimentation and aggregation. Next, an appropriate amount of coupling agent is added to the dispersion, and the surface treatment is performed while the coupling agent is hydrolyzed; in this case as well, the surface treatment is performed while causing dispersion to prevent aggregation using a device such as a pin mill or a wire mill.
[0191] The aqueous medium is a medium having water as a main component. For example, the aqueous medium may be water itself, a medium in which a small amount of a surfactant is added to water, a medium in which a pH adjuster is added to water, or a medium in which an organic solvent is added to water.
[0192] The surfactant is preferably a nonionic surfactant such as polyvinyl alcohol. Preferably, the surfactant is added to the aqueous medium so that the concentration of the surfactant is 0.1% by mass to 5.0% by mass.
[0193] Examples of the pH adjuster include inorganic acids such as hydrochloric acid.
[0194] Examples of the organic solvent include alcohols.
[0195] Examples of the coupling agent that can be used in the surface treatment of the magnetic body include silane coupling agents and titanium coupling agents. Among the foregoing, a silane coupling agent is preferred, and a silane coupling agent represented by the following formula (E) is more preferred.
[0196] R m -Si-Y n (E)
[0197] Wherein, R represents an alkoxy group (preferably an alkoxy group having 1 to 3 carbon atoms); m represents an integer from 1 to 3; Y represents an alkyl group (preferably an alkyl group having 2 to 20 carbon atoms), a phenyl group, a vinyl group, an epoxy group, an acrylic group or a methacrylic group; m and n each independently represent an integer from 1 to 3; the condition is that m+n=4.
[0198] Examples of the silane coupling agent represented by formula (E) include:
[0199] Vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, vinyl triacetoxysilane, methyl trimethoxysilane, dimethyl dimethoxysilane Methoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, n-butyltrimethoxysilane, isobutyltrimethoxysilane, trimethylmethoxysilane, n-hexyltrimethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, hydroxypropyltrimethoxysilane, n-hexadecyltrimethoxysilane and n-octadecyltrimethoxysilane.
[0200] Among the foregoing, from the viewpoint of imparting high hydrophobicity to the magnetic body, it is preferable to use an alkyltrialkoxysilane coupling agent represented by the following general formula (F).
[0201] C p H 2p+1 -Si-(OC q H 2q+1 ) 3 (F)
[0202] Here, p represents an integer of 2 to 20, and q represents an integer of 1 to 3.
[0203] When p in formula (F) is 2 or more, sufficient hydrophobicity can be imparted to the magnetic body. When p is 20 or less, aggregation of the magnetic body can be suppressed. When q is 3 or less, the reactivity of the silane coupling agent is good, and sufficient hydrophobicity can be imparted to the magnetic body.
[0204] Preferably, p in formula (F) is an integer of 3 to 15, and q is preferably 1 or 2.
[0205] When a hydrophobizing agent such as a silane coupling agent is used, the treatment may be performed using one agent alone or two or more agents in combination. When two or more agents are used in combination, the hydrophobizing agents may be used separately or simultaneously for treatment.
[0206] The total treatment amount of the coupling agent used is preferably 0.9 to 3.0 parts by mass relative to 100 parts by mass of the magnetic body; the amount of the treatment agent can be adjusted, for example, according to the surface area of the magnetic body and the reactivity of the coupling agent.
[0207] Examples of the colorant other than the magnetic body include the following.
[0208] Carbon blacks, such as furnace black, channel black, acetylene black, thermal black and lamp black.
[0209] Pigments and dyes can be used as yellow colorants. Examples of pigments include CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 17, 23, 62, 65, 73, 74, 81, 83, 93, 94, 95, 97, 98, 109, 110, 111, 117, 120, 127, 128, 129, 137, 138, 139, 147, 151, 154, 155, 167, 168, 173, 174, 176, 180, 181, 183 and 191, and CI Vat Yellow 1, 3 and 20.
[0210] Examples of the dye include CI Solvent Yellow 19, 44, 77, 79, 81, 82, 93, 98, 103, 104, 112, and 162. The foregoing may be used alone or, alternatively, two or more may be used in combination.
[0211] Pigments and dyes can be used as cyan colorants. Examples of pigments include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 16, 17, 60, 62, and 66; CI Vat Blue 6; and CI Acid Blue 45.
[0212] Examples of the dye include CI Solvent Blue 25, 36, 60, 70, 93, and 95. The foregoing may be used alone or, alternatively, two or more may be used in combination.
[0213] Pigments and dyes can be used as magenta colorants. Examples of pigments include CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57, 57:1, 58, 60, 63, 64, 68, 81, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 150, 163, 166, 169, 177, 184, 185, 202, 206, 207, 209, 220, 221, 238 and 254; and CI Pigment Violet 19; and CI Vat Red 1, 2, 10, 13, 15, 23, 29 and 35.
[0214] Examples of the dye include oil-soluble dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 52, 58, 63, 81, 82, 83, 84, 100, 109, 111, 121, and 122; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, and 27; and basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, and 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, and 28. The foregoing may be used alone or, alternatively, two or more may be used in combination.
[0215] Preferably, the content of the colorant other than the magnetic body in the toner particles is 0.5 parts by mass to 20 parts by mass relative to 100 parts by mass of the resin component of the toner particles.
[0216] The toner particles may contain a releasing agent.
[0217] Examples of release agents include:
[0218] Waxes having fatty acid esters as main components, such as carnauba wax and montanate wax;
[0219] Completely or partially deacidified products of fatty acid esters, for example deacidified carnauba wax;
[0220] Methyl ester compounds having a hydroxyl group obtained by hydrogenation of vegetable oils and fats;
[0221] Saturated fatty acid monoesters, such as stearyl stearate and behenyl behenate;
[0222] Di-esterification products of saturated aliphatic dicarboxylic acids and saturated aliphatic alcohols, such as dibehenyl sebacate, distearyl dodecanedioate and distearyl octadecanediolate;
[0223] Di-esterification products of saturated aliphatic diols and saturated fatty acids, such as nonanediol dibehenate and dodecanediol distearate;
[0224] Aliphatic hydrocarbon waxes, such as low molecular weight polyethylene, low molecular weight polypropylene, microcrystalline wax, paraffin wax and Fischer-Tropsch wax;
[0225] Oxidized aliphatic hydrocarbon waxes, such as oxidized polyethylene waxes, or block copolymers thereof;
[0226] Waxes obtained by grafting vinyl monomers such as styrene or acrylic acid onto aliphatic hydrocarbon waxes;
[0227] saturated straight-chain fatty acids, such as palmitic, stearic, and montanic acids;
[0228] unsaturated fatty acids, such as brassinoic acid, eleostearic acid, and stearidonic acid;
[0229] Saturated alcohols, such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, cetyl alcohol, and myristyl alcohol;
[0230] polyols, such as sorbitol;
[0231] Fatty acid amides, such as linoleamide, oleamide, and lauramide;
[0232] Saturated fatty acid bisamides, such as methylene bis(stearamide), ethylene bis(capramide), ethylene bis(lauramide), and hexamethylene bis(stearamide); unsaturated fatty acid amides, such as ethylene bis(oleamide), hexamethylene bis(oleamide) and N,N'-dioleyl adipamide and N,N'-dioleyl sebacamide;
[0233] Aromatic bisamides, such as meta-xylene bis(stearamide), and N,N'-distearyl isophthalamide;
[0234] Fatty acid metal salts (generally referred to as metal soaps), such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; and
[0235] A long-chain alkyl alcohol or a long-chain alkyl carboxylic acid having 12 or more carbon atoms.
[0236] Preferred among these release agents are monofunctional or difunctional ester waxes such as monoesters or diesters of saturated fatty acids, and hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax.
[0237] The release agent may be used alone or, alternatively, two or more kinds may be used in combination.
[0238] The melting point of the release agent, which is defined by the peak temperature of the maximum endothermic peak at temperature rise and measured using a differential scanning calorimeter (DSC), is preferably 60° C. to 140° C. The melting point is more preferably 60° C. to 90° C. When the melting point is 60° C. or higher, the storability of the toner is improved. On the contrary, when the melting point is 140° C. or lower, the low-temperature fixability can be easily improved.
[0239] The content of the release agent in the toner particles is preferably 3 to 30 parts by mass relative to 100 parts by mass of the resin component in the toner particles. When the content of the release agent is 3 parts by mass or more, the fixing performance is easily improved. On the contrary, when the content of the release agent is 30 parts by mass or less, the toner is less likely to deteriorate after long-term use, and the image stability is easily improved.
[0240] The toner particles can be used as a toner as they are. Various external additives such as inorganic fine particles may also be added to the toner particles to obtain a toner. Organic fine particles may be used instead of or in addition to the inorganic fine particles.
[0241] Examples of inorganic fine particles include lubricants such as silica fine particles, fluororesin particles, zinc stearate particles and polyvinylidene fluoride particles; and abrasives such as cerium oxide particles, silicon carbide particles, and fine particles of alkaline earth metal titanates, specifically, strontium titanate fine particles, barium titanate fine particles and calcium titanate fine particles, etc.
[0242] A small amount of spacer particles such as silica may also be used within the extent that the effects of the present invention are not impaired. Among them, silica fine particles are desirable because they significantly improve the fluidity of the toner and make it easier to obtain the effects of the present invention.
[0243] When silica fine particles are used, the specific surface area measured by the BET method using nitrogen adsorption (BET specific surface area) is preferably 20 m 2 / g to 350m 2 / g, or more preferably 25m 2 / g to 300m 2 / g, thereby imparting good fluidity to the toner.
[0244] The specific surface area measured by the BET method using nitrogen adsorption (BET specific surface area) is measured according to JIS Z 8830 (2001). "Automatic specific surface area and pore distribution measuring apparatus TriStar 3000 (Shimadzu Corporation)" can be used as a measuring system for gas adsorption measurement by a constant volume method.
[0245] The silica fine particle or other inorganic fine particle is preferably one subjected to a hydrophobization treatment, and particularly one subjected to a hydrophobization treatment so that the hydrophobicity measured by a methanol titration test is 40% or more, or more preferably 50% or more.
[0246] Examples of the method of hydrophobizing treatment include a method of treating with an organic silicon compound, silicone oil, a long-chain fatty acid, or the like.
[0247] Examples of the organosilicon compound include hexamethyldisilazane, trimethylsilane, trimethylethoxysilane, isobutyltrimethoxysilane, trimethylchlorosilane, dimethyldichlorosilane, methyltrichlorosilane, dimethylethoxysilane, dimethyldimethoxysilane, diphenyldiethoxysilane, and hexamethyldisiloxane, etc. One or a mixture of two or more of these organosilicon compounds may be used.
[0248] Examples of the silicone oil include dimethyl silicone oil, methylphenyl silicone oil, α-methylstyrene-modified silicone oil, chlorophenyl silicone oil, fluorine-modified silicone oil, and the like.
[0249] C 10-22 Fatty acid is advantageously used as long-chain fatty acid, and straight-chain or branched fatty acid can be used. In addition, saturated or unsaturated fatty acid can be used.
[0250] Among them, from the viewpoint of promoting uniform treatment of the surface of the inorganic fine particles, C 10-22 Straight chain saturated fatty acids are highly desirable.
[0251] Examples of straight-chain saturated fatty acids include capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid and the like.
[0252] Among the inorganic fine particles, silica fine particles are preferably one treated with silicone oil, and silica fine particles treated with an organic silicon compound and silicone oil are more preferred because it makes it easy to control the hydrophobicity.
[0253] Methods for treating silica fine particles with silicone oil include a method of directly mixing silicone oil with silica fine particles treated with an organic silicon compound using a mixer such as a Henschel mixer, and a method of spraying silica fine particles with silicone oil. Another method is to dissolve or disperse silicone oil in an appropriate solvent, add and mix silica fine particles, and then remove the solvent.
[0254] The amount of the silicone oil used in the treatment is preferably 1 part by mass to 40 parts by mass, or more preferably 3 parts by mass to 35 parts by mass relative to 100 parts by mass of the silica fine particles in order to obtain good hydrophobicity.
[0255] Next, the method of measuring physical properties will be described.
[0256] <Analysis Method of Monomers of Resin Components Such as Non-crystalline Polyester and Crystalline Polyester>
[0257] (Separation of resin component and release agent from toner)
[0258] The toner is dissolved in tetrahydrofuran (THF), and the solvent is distilled off from the obtained soluble matter under reduced pressure to obtain the tetrahydrofuran (THF) soluble component of the toner. The obtained tetrahydrofuran (THF) soluble component of the toner is dissolved in chloroform to prepare a sample solution with a concentration of 25 mg / mL. 3.5 mL of the obtained sample solution is injected into the following equipment, and the low molecular weight component derived from the release agent with a molecular weight of less than 2000 and the high molecular weight component derived from the resin component with a molecular weight of more than 2000 are separated under the following conditions.
[0259] Preparative GPC equipment: Preparative HPLC LC-980, Japan Analytical Industry Co., Ltd.
[0260] Preparative columns: JAIGEL 3H, JAIGEL 5H (Japan Analytical Industry Co., Ltd.)
[0261] Eluent: Chloroform
[0262] Flow rate: 3.5mL / min
[0263] Once the high molecular weight component derived from the resin component was separated, the solvent was distilled off under reduced pressure, and the component was further dried under reduced pressure in an atmosphere of 90° C. for 24 hours. This operation was repeated until about 100 mg of the resin component was obtained.
[0264] (Separation of non-crystalline polyester and crystalline polyester from resin components)
[0265] 500 mL of acetone was added to 100 mg of the resin component obtained by the above operation, and then completely melted by heating to 70° C., and gradually cooled to 25° C. to recrystallize the crystalline resin. The crystalline resin was suction filtered and separated into a crystalline polyester and a filtrate.
[0266] The separated filtrate was gradually added to 500 mL of methanol to reprecipitate the non-crystalline polyester, and then the non-crystalline polyester was extracted with a suction filter.
[0267] The obtained non-crystalline polyester and crystalline polyester were dried under reduced pressure at 40° C. for 24 hours.
[0268] (e.g. monomer analysis of resin components such as non-crystalline polyester and crystalline polyester)
[0269] A sample of the resin component such as the non-crystalline polyester and the crystalline polyester separated from the toner is analyzed with a pyrolysis GC / MS apparatus under the following conditions to determine the kind of monomers in the resin component such as the non-crystalline polyester and the crystalline polyester.
[0270] Measuring equipment: "Voyager" (product name, Thermo Electron Co., Ltd.)
[0271] Pyrolysis temperature: 600℃
[0272] Column: HP-1 (15m×0.25mm×0.25μm)
[0273] Inlet: 300℃, split flow: 20.0
[0274] Injection volume: 1.2mL / min
[0275] Heating: 50℃(4min)-300℃(20℃ / min)
[0276] Depth distribution measurement of secondary ions on the toner particle surface by time-of-flight secondary ion mass spectrometry TOF-SIMS
[0277] The depth distribution of ions derived from the resin constituting the toner particles was measured using a TOF-SIMS apparatus (Ulvac-Phi, Inc.) The conditions were as follows.
[0278] (Sample Preparation)
[0279] An indium plate is placed on a sample holder and toner particles are attached to the indium plate. When the toner particles are moving on the sample holder, an indium plate may also be placed on the sample holder and coated with carbon paste before the toner particles are fixed. When a fixing aid such as carbon paste or silicon wafer is used, the background is measured under the same conditions without toner particles and used for conversion.
[0280] (Sputtering conditions)
[0281] Sputtering ion type: Argon ion cluster ((Ar n ) + , n = about 2000)
[0282] Accelerating voltage: 10 kV
[0283] Current value: 8.5nA
[0284] Sputtering area: 600×600μm 2
[0285] Sputtering time: 2sec / cycle
[0286] Sputtering rate: 1nm / sec
[0287] Regarding the above sputtering rate, polymethyl methacrylate resin was sputtered to a film thickness of 300 nm under the above conditions, and the time taken to complete sputtering of 300 nm was calculated and used for conversion by normalization.
[0288] (Analysis conditions)
[0289] Primary ion type: gold ion (Au + )
[0290] Accelerating voltage: 25 kV
[0291] Current value: 2pA
[0292] Analysis area: 200×200μm 2
[0293] Number of pixels: 256×256 pixels
[0294] Analysis time: 30 sec / cycle
[0295] Repetition frequency: 8.2kHz
[0296] Charge neutralization: On
[0297] Secondary ion polarity: positive
[0298] Secondary ion mass range: m / z 0.5 to 1850
[0299] Calculation of the secondary ion intensity derived from the resin component at a depth of t (nm) from the toner particle surface
[0300] Calculation of Ia(t)
[0301] The monomer species in the non-crystalline polyester are identified by the above monomer analysis, and one or more peaks in the mass spectrum of the non-crystalline polyester that are not attributed to other toner materials are selected. The total of these mass spectrum intensities at a depth of t (nm) from the toner particle surface is taken as Ia(t).
[0302] Calculation of Ic(t)
[0303] The monomer species in the crystalline polyester are identified by the above monomer analysis, and one or more peaks in the mass spectrum of the crystalline polyester that are not attributed to other toner materials are selected. The total of these mass spectrum intensities at a depth of t (nm) from the toner particle surface is taken as Ic (t).
[0304] Calculation of Is(t)
[0305] The monomer species in the styrene acrylic resin are identified by the above monomer analysis, and one or more peaks in the mass spectrum of the styrene acrylic resin that are not attributed to other toner materials are selected. The intensity of the mass spectrum at a depth of t (nm) from the toner particle surface is taken as Is(t).
[0306] Calculation of I(t)
[0307] The resin component used in the toner particles is identified by the above monomer analysis, and all mass spectra derived from the resin are selected. The total of the mass spectrum intensity at a depth of t (nm) from the toner particle surface is taken as I(t).
[0308] (Separation of toner particles and toner)
[0309] The above measurement can also be performed using toner particles separated from the toner as follows.
[0310] 160g of sucrose (Kishida Chemical Co., Ltd.) is added to 100mL of ion exchange water and dissolved while boiling water to prepare sucrose thick liquid. 31g of this sucrose thick liquid and 6mL of Contaminon N (pH is 7 precision measuring instrument cleaning neutral detergent 10 mass % aqueous solution, the detergent comprises nonionic surfactant, anionic surfactant and organic detergent, manufactured by Wako Pure Chemical Industries, Ltd.) are put into 50mL centrifuge tube. 1.0g of toner is added thereto, and toner agglomerates are crushed with a spatula etc. In a shaking table (AS-1N, sold by AS ONE Corporation), the centrifuge tube is shaken at 300spm (strokes per minute) for 20 minutes. After shaking, the solution was transferred to a 50 mL glass tube for a swing rotor, and separated in a centrifuge (H-9R, Kokusan Co., Ltd.) at 3,500 rpm for 30 minutes.
[0311] The toner particles are separated from the external additive by this operation. The thorough separation of the toner particles from the aqueous solution is visually confirmed, and the toner particles separated in the uppermost layer are collected with a scraper or the like. The collected toner particles are filtered with a vacuum filter and dried in a dryer for a minimum of 1 hour to obtain a measurement sample. This operation is performed multiple times to ensure the required amount.
[0312] <Method for measuring weight average particle size (D4)>
[0313] A precision particle size distribution measuring device relying on the pore resistance method and equipped with a 100 μm orifice tube (product name: Coulter Counter Multisizer 3, manufactured by Beckman Coulter, Inc.) was used, and
[0314] The weight average particle diameter (D4) of the toner particles is calculated by analyzing the measurement data obtained by measuring with 25,000 effective measurement channels using dedicated software attached to the device for setting measurement conditions and analyzing measurement data (product name: Beckman Coulter Multisizer 3, version 3.51, manufactured by Beckman Coulter, Inc.).
[0315] The electrolyte aqueous solution used for measurement can be prepared by dissolving special grade sodium chloride in ion exchange water to a concentration of about 1 mass %; here, for example, ISOTON II (product name) manufactured by Beckman Coulter, Inc. can be used as the electrolyte aqueous solution.
[0316] Prior to measurement and analysis, the dedicated software was set up as follows.
[0317] In the "Screen for Changing the Standard Operating Method (SOM)" of the dedicated software, set the total count of the control mode to 50,000 particles; set the number of runs to 1, and set the Kd value to the value obtained using the "Standard Particles 10.0 μm" (manufactured by BeckmanCoulter). Press the "Threshold / Noise Level" measurement button to automatically set the threshold and noise level. Then set the current to 1600 μA, the gain to 2, the electrolyte solution to ISOTON II (product name), and check the flushing of the mouth tube after measurement.
[0318] In the "Pulse to Particle Size Conversion Setting Screen" of the dedicated software, set the element interval to logarithmic particle size, set the particle size element to 256 particle size elements, and set the particle size range to the range of 2 μm to 60 μm.
[0319] The specific measurement method is described as follows.
[0320] (1) Here, about 200 mL of electrolyte aqueous solution is placed in a 250 mL round-bottom glass beaker dedicated to Multisizer 3. The beaker is placed on the sample stage and stirred counterclockwise with a stirring rod at 24 revolutions per second. Then, dirt and bubbles are removed from the nozzle using the "Opioid Rinse" function of the dedicated software.
[0321] (2) Then, about 30 mL of the electrolyte aqueous solution was placed in a 100 mL flat-bottom glass beaker. About 0.3 mL of a dilution of "Contaminon N" (product name) manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., which was diluted three times by mass in ion exchange water, was added to the solution as a dispersant. Contaminon N (product name) is a 10% by mass aqueous solution of a neutral detergent for precision measuring instruments having a pH of 7, and is composed of a nonionic surfactant, an anionic surfactant, and an organic detergent.
[0322] (3) A predetermined amount of ion exchange water was placed in a water tank of an ultrasonic disperser (product name: Ultrasonic Dispersion System Tetora 150, manufactured by Nikkaki Bios Co., Ltd.), and about 2 mL of the above-mentioned Contaminon N (product name) was added to the water tank. Ultrasonic Dispersion System Tetora 150 is an ultrasonic disperser having a power output of 120 W and internally equipped with two oscillators oscillating at a frequency of 50 kHz and arranged with a phase shift of 180 degrees.
[0323] (4) The beaker in (2) is set in the beaker fixing hole of the ultrasonic disperser, and then the ultrasonic disperser is operated. The height position of the beaker is adjusted to maximize the resonance state of the liquid surface of the aqueous electrolyte solution in the beaker.
[0324] (5) While the electrolyte aqueous solution in the beaker of (4) is irradiated with ultrasonic waves, about 10 mg of the toner particles are then gradually added to the electrolyte aqueous solution to be dispersed therein. The ultrasonic dispersion treatment is continued for another 60 seconds. The water temperature of the water tank during the ultrasonic dispersion is appropriately adjusted within a range of 10° C. to 40° C.
[0325] (6) Using a pipette, the electrolyte aqueous solution containing the dispersed toner particles in (5) is added dropwise to the round-bottomed beaker provided in the sample stage in (1) to adjust the measurement concentration to about 5%. Then, measurement is performed until the number of particles measured reaches 50,000.
[0326] (7) Use the dedicated software attached to the equipment to analyze the measured data to calculate the weight average particle size (D4). When selecting Graph / Volume % in the dedicated software, the "Average Diameter" in the "Analysis / Volume Statistics (Arithmetic Mean)" interface is the weight average particle size (D4).
[0327] <Measurement of Melting Point Tm of Crystalline Polyester>
[0328] The peak temperature of the maximum endothermic peak of the crystalline polyester is measured using a differential scanning calorimeter "Q1000" (TA Instruments) in accordance with ASTM D3418-82.
[0329] The melting points of indium and zinc were used for temperature calibration of the detector, and the heat of fusion of indium was used for caloric calibration.
[0330] Specifically, about 1 mg of the crystalline polyester was accurately weighed and placed in an aluminum pan, and an empty aluminum pan was used as a reference, and the measurement was performed at a temperature increase rate of 10°C / min in the temperature range of 30°C to 200°C. During the measurement, the temperature was once increased to 200°C, then decreased to 30°C, and then increased again. The maximum endothermic peak in the DSC curve in the range of 30°C to 200°C during this second temperature increase step was taken as the maximum endothermic peak of the endothermic curve in the DSC measurement of the crystalline polyester.
[0331] Measurement of glass transition temperature (Tg) of toner
[0332] The glass transition temperature (Tg) was measured using a differential scanning calorimeter "Q1000" (TA Instruments). The melting points of indium and zinc were used for temperature correction of the detector, and the heat of fusion of indium was used for heat correction. Specifically, about 3 mg of the toner was accurately weighed and placed in an aluminum pan, and an empty aluminum pan was used as a reference, and the measurement was performed at a temperature increase rate of 10°C / min in a temperature range of 30°C to 200°C.
[0333] The specific heat change is obtained during this temperature raising step in the temperature range of 40° C. to 100° C. The glass transition temperature is the temperature at the intersection between the differential thermal curve and a line drawn at the midpoint between the base lines before and after the occurrence of the specific heat change.
[0334] <Measurement of Acid Value of Crystalline Polyester>
[0335] The acid value refers to the number of mg of potassium hydroxide required to neutralize the acid contained in 1 gram of a sample. The acid value of the crystalline polyester is measured in accordance with JIS K0070-1992 and specifically according to the following procedures.
[0336] (1) Reagent preparation
[0337] Here, 1.0 g of phenolphthalein was dissolved in 90 ml of ethanol (95 vol%), and ion-exchanged water was added until it reached 100 ml to obtain a phenolphthalein solution.
[0338] Then, 7g of special grade potassium hydroxide is dissolved in 5mL water, and ethanol (95vol%) is added until 1 liter is reached. In order to avoid contact with carbon dioxide etc., the resulting solution is put into an alkali-resistant container and allowed to stand for 3 days, and then the solution is filtered to obtain potassium hydroxide solution. The potassium hydroxide solution obtained is stored in an alkali-resistant container. Then 25ml of 0.1mol / L hydrochloric acid is put into a conical flask, a few drops of phenolphthalein solution are added thereto, and potassium hydroxide solution is used for titration. Then the factor of potassium hydroxide solution is calculated from the amount of potassium hydroxide solution required for neutralization. The hydrochloric acid of 0.1mol / L above is prepared according to JIS K8001-1998.
[0339] (2) Operation
[0340] (A) Main test
[0341] Here, 2.0 g of a sample of crushed crystalline polyester is accurately weighed in a 200 mL conical flask, and 100 ml of a mixed solution of toluene / ethanol (2:1) is added to dissolve the sample for 5 hours. Next, a few drops of phenolphthalein solution are added as an indicator, and titration is performed using a potassium hydroxide solution. The endpoint of the titration is the time point when the light red color of the indicator lasts for about 30 seconds.
[0342] (B) Blank test
[0343] Titration was performed according to the same operation as described above, except that no sample was used here (ie, by using only a mixed solution of toluene / ethanol (2:1)).
[0344] (3) The acid value was calculated by substituting the obtained result into the following expression:
[0345] A=[(CB)×f×5.61] / S
[0346] In the expression, A is the acid value (mgKOH / g), B is the amount of potassium hydroxide solution added in the blank test (mL), C is the amount of potassium hydroxide solution added in the main test (mL), f is the factor of the potassium hydroxide solution, and S is the mass of the sample (g).
[0347] Measurement of Molecular Weight Distribution of Non-Crystalline Polyester, Crystalline Polyester and Toner Particles
[0348] The molecular weight distribution of THF-soluble matter in the toner, the non-crystalline polyester resin, and the crystalline polyester resin is measured by gel permeation chromatography (GPC) as follows.
[0349] First, the sample was dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The obtained solution was filtered through a solvent-resistant membrane filter "Sample Pretreatment Box" (Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution was adjusted to a concentration of THF-soluble components of about 0.8% by mass. The sample solution was used for measurement under the following conditions.
[0350] Instrument: HLC8120 GPC (detector: RI) (Tosoh Corporation)
[0351] Column: Shodex KF-801, 802, 803, 804, 805, 806, and 807 7-column (Showa Denko KK)
[0352] Eluent: Tetrahydrofuran (THF)
[0353] Flow rate: 1.0mL / min
[0354] Oven temperature: 40.0℃
[0355] Sample injection volume: 0.10mL
[0356] The molecular weight of the sample is determined using a molecular weight calibration curve constructed using a standard polystyrene resin (e.g., product name: "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, and A-500", Tosoh Corporation).
[0357] Measurement of the content of styrene acrylic resin in the resin component of toner
[0358] In order to measure the content of the styrene acrylic resin in the resin component of the toner, the content of the styrene acrylic resin was measured by nuclear magnetic resonance spectroscopy under the following conditions: 1 H-NMR) [400 MHz, CDCl 3 , room temperature (25° C.)] A sample of the resin component separated from the toner was analyzed.
[0359] Measuring device: FT NMR device JNM-EX400 (JEOL Ltd.)
[0360] Measuring frequency: 400MHz
[0361] Pulse condition: 5.0μs
[0362] Frequency range: 10500Hz
[0363] Cumulative times: 64 times
[0364] The content of the styrene acrylic resin in the resin component of the toner is calculated on a mass basis from the integrated value of the obtained spectrum.
[0365] Example
[0366] The present invention is explained in detail below using Examples, but the present invention is not limited thereto. Unless otherwise specified, the parts in the following formulations are based on mass.
[0367] <Production Example of Crystalline Polyester CPES1>
[0368] 45 mol% of 1,9-nonanediol and 55 mol% of sebacic acid were placed in a reaction tank equipped with a nitrogen inlet pipe, a dehydration pipe, a stirrer and a thermocouple, 1 part of tin dioctanoate was added as a catalyst relative to 100 parts of all monomers, and the mixture was heated to 140°C under a nitrogen atmosphere and reacted for 6 hours while distilling off water at normal pressure. Next, the temperature was raised to 200°C at 10°C / hour to react the mixture, and then once the temperature reached 200°C, it was further reacted for 2 hours, after which the pressure in the reaction tank was reduced to less than 5 kPa and the reaction was continued at 200°C while monitoring the molecular weight to obtain crystalline polyester CPES1. The weight average molecular weight (Mw) of CPES1 was 39100.
[0369] <Production Example of Crystalline Polyesters CPES2 to CPES11>
[0370] In the production example of crystalline polyester CPES1, the monomer composition was changed as shown in Table 1 to obtain crystalline polyesters CPES2 to CPES11. The molar ratio of the alcohol monomer to the acid monomer was the same as that of CPES1.
[0371] <Production Example of Crystalline Polyester CPES12>
[0372] Production of vinyl polymer 1
[0373] In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet pipe and a pressure reducing device, 50.0 parts of xylene were heated under nitrogen purge and refluxed at a liquid temperature of 140°C. A mixture of 100.0 parts of styrene and 8.0 parts of 2,2'-azobis(2-methylpropionic acid)dimethyl ester as a polymerization initiator was added dropwise to the reaction vessel over a period of 3 hours, and after the addition was completed, the solution was stirred for 3 hours. Then, xylene and the remaining styrene were distilled off at 160°C and 1 hPa to obtain a vinyl polymer 1. The weight average molecular weight (Mw) of the obtained vinyl polymer measured by gel permeation chromatography (GPC) was 8000.
[0374] 100.0 parts of vinyl polymer 1, 128.0 parts of xylene as an organic solvent, and 78.0 parts of 1,14-tetradecanediol were added to a reaction vessel equipped with a stirrer, a thermometer, a nitrogen introduction tube, a dehydration tube, and a pressure reducing device. 0.6 parts of isopropoxytitanium (IV) was further added as an esterification catalyst, and the mixture was reacted at 150° C. in a nitrogen atmosphere for 4 hours. Then 83.3 parts of tetradecanedioic acid were added, and the mixture was reacted at 150° C. for 3 hours and at 180° C. for 4 hours.
[0375] Then, the mixture was reacted at 180° C. and 1 hPa until a desired weight average molecular weight (Mw) was obtained to obtain CPES 12. The physical properties are shown in Table 1.
[0376] [Table 1]
[0377]
[0378] In the table, the acid value is given in mg KOH / g and the SP value is given in (cal / cm 3 ) 1 / 2 The units are given.
[0379] <Production Example of Non-Crystallinous Polyester APES1>
[0380] The carboxylic acid component and the alcohol component shown in Table 2 were prepared as raw material monomers and placed in a reaction tank equipped with a nitrogen introduction tube, a dehydration tube, a stirrer and a thermocouple, and then dibutyltin was added as a catalyst in an amount of 1.5 parts relative to 100 parts of all monomers. The temperature was then rapidly raised to 180° C. under nitrogen atmosphere at normal pressure, and then raised from 180° C. to 210° C. at a rate of 10° C. / hour while distilling off water to perform polycondensation.
[0381] Once reaching 210°C, the reaction tank was depressurized to 5 kPa or less, and polycondensation was performed at 210°C and 5 kPa or less to obtain non-crystalline polyester APES1. The polymerization time was adjusted during this process to obtain the weight average molecular weight (Mw) shown in Table 2. The physical properties are shown in Table 2.
[0382] <Production Example of Non-Crystallinity Polyesters APES2 to APES7>
[0383] In the production example of the non-crystalline polyester APES1, the monomer composition was changed as shown in Table 2 to obtain non-crystalline polyesters APES2 to APES7.
[0384] <Production Example of Non-Crystallinity Polyester APES8>
[0385] 100 parts of a mixture of raw material monomers other than trimellitic anhydride in the amounts shown in Table 2 and 0.52 parts of tin di(2-ethylhexanoate) were placed in a polymerization tank equipped with a nitrogen introduction line, a dehydration line, and a stirrer. The inside of the polymerization tank was replaced with a nitrogen atmosphere, and then a polycondensation reaction was performed while heating at 200° C. for 6 hours. The temperature was then raised to 210° C., trimellitic anhydride was added, and the polymerization tank was depressurized to 40 kPa, and then a further condensation reaction was performed to obtain APES8.
[0386] <Production Example of Non-Crystallinity Polyester APES9>
[0387] The raw material monomers as shown in Table 2 were added to a reaction tank equipped with a nitrogen introduction tube, a dehydration tube, a stirrer and a thermocouple. The inside of the reaction tank was then replaced with nitrogen, and the temperature was gradually increased under stirring, and the mixture was reacted for 4 hours while continuing to stir at 200°C. The pressure inside the reaction tank was reduced to 8.3 kPa and maintained for 1 hour, after which the mixture was cooled to 160°C and returned to atmospheric pressure. Tert-butylcatechol (reaction inhibitor) was then added in an amount of 0.1 parts relative to 100 parts of all monomers, the pressure inside the reaction tank was reduced to 8.3 kPa, the temperature was maintained at 180°C, the mixture was reacted for 1 hour, and once it was confirmed that the softening point reached 90°C, the temperature was reduced to stop the reaction and non-crystalline polyester APES9 was obtained.
[0388] <Production Example of Non-Crystallinity Polyester APES10>
[0389] The non-crystalline polyester APES10 was obtained by changing the monomer composition as shown in Table 2 in the production example of the non-crystalline polyester APES9.
[0390] [Table 2]
[0391]
[0392] PO stands for propylene oxide.
[0393] <Production Example of Treated Magnetic Body>
[0394] In an aqueous solution of ferrous sulfate, 1.00 to 1.10 equivalents of sodium hydroxide solution relative to iron atoms, 0.15 mass % of phosphorus atoms relative to iron atoms, and 2 O 5 , and SiO in an amount of 0.50 mass % in terms of silicon atoms relative to iron atoms 2 After that, an aqueous solution containing ferrous hydroxide was prepared. The pH of the aqueous solution was adjusted to 8.0, and an oxidation reaction was performed at 85° C. while blowing air to prepare a slurry having seed crystals.
[0395] Next, an aqueous solution of ferrous sulfate was added to the slurry in an amount of 0.90 to 1.20 equivalents relative to the initial alkali amount (sodium component of sodium hydroxide). Thereafter, the slurry was maintained at pH 7.6 and an oxidation reaction was performed while blowing air to prepare a slurry containing magnetic iron oxide.
[0396] The obtained slurry is filtered and washed, and then the aqueous slurry is temporarily recovered. At this time, a small amount of the aqueous slurry is sampled and the water content is measured.
[0397] Next, the aqueous slurry was put into another aqueous medium without drying, and redispersed in a pin mill while stirring the slurry and causing circulation, and the pH of the redispersed liquid was adjusted to about 4.8.
[0398] Then, while stirring, 1.6 parts of n-hexyltrimethoxysilane coupling agent was added to 100 parts of magnetic iron oxide (the amount of magnetic iron oxide was calculated by subtracting the water content from the aqueous slurry) to cause hydrolysis. Surface treatment was then performed by stirring and setting the pH of the dispersion to 8.6. The resulting hydrophobic magnetic body was filtered using a filter press, washed with a large amount of water, and then dried at 100°C for 15 minutes and then at 90°C for 30 minutes. Thereafter, the obtained particles were crushed to obtain a treated magnetic body having a volume average particle size of 0.21 μm.
[0399] <Production Example of Toner Particles 1>
[0400] 450 parts of 0.1 mol / L Na 3 PO 4 The aqueous solution was added to 720 parts of ion exchange water and heated to 60°C, after which 67.7 parts of 1.0 mol / L CaCl 2 aqueous solution to obtain an aqueous medium containing a dispersant.
[0401]
[0402] These materials were uniformly dispersed and mixed with a grinder (Mitsui Miike Kakoki Corporation) to obtain a polymerizable monomer composition. The polymerizable monomer composition was heated to 63° C., and 15.0 parts of paraffin wax (HNP-51, Nippon Seiro Co., Ltd., melting point 74° C.) and 15 parts of CPES1 were added, mixed and dissolved. Then 7.0 parts of a polymerization initiator, tert-butyl peroxypivalate, was dissolved therein.
[0403] The polymerizable monomer composition was then added to the above aqueous medium and stirred at 12,000 rpm for 10 minutes at 60° C. in a nitrogen atmosphere using a TK homogenizer (Tokushu Kika Kogyo Co., Ltd.) to form particles (granulation).
[0404] Then, the mixture was reacted at 74° C. for 4 hours while being stirred with a paddle stirring blade.
[0405] Next, the temperature of the aqueous medium was raised to 100° C. and maintained for 120 minutes. It was then cooled to room temperature at a rate of 3° C. per minute, hydrochloric acid was added to dissolve the dispersant, and the mixture was filtered, washed with water, and dried to obtain toner particles 1 having a weight average particle size (D4) of 6.7 μm.
[0406] Table 3 shows the production conditions of the obtained toner particles 1.
[0407] <Manufacturing Example of Toner Particles 2 to 15, 17 and 18 and Comparative Toner Particles 1 to 6, 9 and 10>
[0408] Toner particles 2 to 15, 17 and 18 and comparative toner particles 1 to 6, 9 and 10 were produced as in the production example of toner particle 1 except that the non-crystalline polyester and the crystalline polyester were changed.
[0409] <Production Example of Toner Particles 16>
[0410]
[0411] The above solution was put into a container, and stirred and dispersed with Homo Disper (Tokushu Kika Kogyo Co., Ltd.) at 2000 rpm for 5 minutes to prepare an oil phase.
[0412] In another container, 390.0 parts of 0.1 mol / L sodium phosphate (Na 3 PO 4 ) aqueous solution was added to 1152.0 parts of ion exchange water and stirred with Clearmix (M Technique Co., Ltd.) while heating to 70°C. Then 58.0 parts of 1.0 mol / L calcium chloride (CaCl 2 ) aqueous solution, and continue stirring to produce a solution containing tricalcium phosphate (Ca 3 (PO 4 ) 2 ) and prepare an aqueous medium.
[0413] The oil phase was then added to the aqueous phase, and granulation was performed by stirring at 10000 rpm for 10 minutes at 60° C. in a nitrogen atmosphere with Clearmix (M Technique Co., Ltd.). The resulting suspension was then stirred at a rotation speed of 150 rpm with a paddle stirring blade while removing the solvent at 80° C. under a reduced pressure of 400 mbar over the course of 5 hours. The suspension was then cooled to 25° C., ion exchange water was added to adjust the solid concentration of the dispersion to 20% by mass, and toner slurry 1 was obtained.
[0414] The toner slurry 1 was cooled to 25° C., hydrochloric acid was added to a pH of 1.5, and the slurry was stirred for 2 hours. It was then filtered, washed with water, and dried to obtain toner particles 16 .
[0415] <Production Example of Comparative Toner Particles 7>
[0416] [Preparation of Crystalline Polyester Dispersion Liquid 1]
[0417] 100.0 parts of CPES1, 90.0 parts of toluene and 2.0 parts of diethylaminoethanol were charged into a reaction vessel equipped with a stirrer, a condenser, a thermometer and a nitrogen introduction tube, and heated to 80°C to dissolve the mixture. Then 300.0 parts of ion exchange water were gradually added at 80°C under stirring to perform phase inversion emulsification, and the resulting aqueous dispersion was transferred to a distillation apparatus and distilled until the distillate temperature was 100°C. After cooling, ion exchange water was added to the resulting aqueous dispersion to adjust the resin concentration of the dispersion to 20%. This was used as crystalline polyester dispersion 1.
[0418] [Preparation of non-crystalline polyester dispersion 1]
[0419] 100.0 parts of APES1, 90.0 parts of toluene and 2.0 parts of diethylaminoethanol were charged into a reaction vessel equipped with a stirrer, a condenser, a thermometer and a nitrogen introduction tube, and heated to 80° C. to dissolve the mixture. Then 300.0 parts of ion exchange water were gradually added under stirring at 80° C. to perform phase inversion emulsification, and the resulting aqueous dispersion was transferred to a distillation apparatus and distilled until the distillate temperature was 100° C. After cooling, ion exchange water was added to the resulting aqueous dispersion to adjust the resin concentration of the dispersion to 20%. This was used as non-crystalline polyester dispersion 1.
[0420] [Preparation of colorant dispersion]
[0421] Carbon black 70.0 parts
[0422] (Nipex35:Orion Engineered Carbons)
[0423] 3.0 parts of anionic surfactant
[0424] (Product name: Neogen SC, DKS Co., Ltd.)
[0425] 400.0 parts of ion exchange water
[0426] These components were mixed and dissolved, and then dispersed with a homogenizer (IKA, Ultra-Turrax) to obtain a colorant dispersion.
[0427] [Preparation of release agent dispersion]
[0428] Paraffin 100.0 parts
[0429] (HNP-51: Nippon Seiro Co., Ltd., melting point 74°C)
[0430] 2.0 parts of anionic surfactant
[0431] (Product name: Pionin A-45-D, Takemoto Oil & Fat Co., Ltd.)
[0432] 500.0 parts of ion exchange water
[0433] These components were mixed and dissolved, dispersed with a homogenizer (IKA, Ultra-Turrax), and then dispersed with a pressure discharge type Gorin homogenizer to obtain a releasing agent dispersion containing dispersed releasing agent fine particles (paraffin wax).
[0434]
[0435] These components were mixed and dispersed with a homogenizer (product name: Ultra-Turrax T50, IKA) in a round bottom stainless steel flask to prepare a mixed solution, which was then heated to 50°C and maintained at 50°C for 30 minutes in a heating oil bath under stirring to form aggregated particles. 60.0 parts of crystalline polyester dispersion 1 and 6.0 parts of anionic surfactant (product name: Neogen SC, DKS Co., Ltd.) were then added to the dispersion with dispersed aggregated particles, which was then heated to 65°C. An appropriate amount of sodium hydroxide was then added to adjust the system to a pH of 7.0, and the mixture was kept as it was for 3 hours to fuse the aggregated particles. It was then cooled to 25°C, ion exchange water was added, and the solid concentration of the dispersion was adjusted to 20% by mass to obtain toner slurry 2.
[0436] This was then sufficiently washed with ion-exchanged water, and then filtered, dried, and classified to obtain Comparative Toner Particles 7.
[0437] <Production Example of Comparative Toner Particles 8>
[0438] Comparative toner particles 8 were obtained as in the production example of comparative toner particles 7 except that CPES8 was used instead of CPES1 and APES8 was used instead of APES1.
[0439] [Table 3]
[0440]
[0441] In the table, "C." means comparison. The addition amount of the non-crystalline polyester and the crystalline polyester is the amount relative to 100 parts of the polymerizable monomer. The content of the styrene acrylic resin is expressed as mass %.
[0442] <Production Example of Toner 1>
[0443] Using a Mitsui Henschel mixer (Mitsui Miike Kakoki Corporation), 100 parts of Toner Particles 1 were mixed with 1.2 parts of a treated toner having a BET specific surface area of 120 m 2 / g of treated hydrophobic silica fine particles obtained by treating silica having a primary particle size of 12 nm with hexamethyldisilazane and then with silicone oil were mixed to prepare Toner 1. The physical properties are shown in Tables 4-1, 4-2, and 4-3.
[0444] <Manufacturing Examples of Toners 2 to 18 and Comparative Toners 1 to 10>
[0445] Toners 2 to 18 and Comparative Toners 1 to 10 were obtained by changing toner particles as shown in Tables 4-1, 4-2, and 4-3 in the production example of Toner 1. The physical properties are shown in Tables 4-1, 4-2, and 4-3.
[0446] [Table 4-1]
[0447]
[0448] [Table 4-2]
[0449]
[0450] [Table 4-3]
[0451]
[0452] In the table, "C." means "Compare".
[0453] Regarding formulas (1) and (5), in each example and each comparative example, each value of Ia(t) and Ic(t) within the range of 0 ≤ t ≤ 10 is a value within the range of values between t = 0 and t = 10.
[0454] Regarding formula (2), in each example and each comparative example, each value of (Ia(t) + Ic(t)) / I(t) within the range of 0 ≤ t ≤ 10 is a value within the range of values between t = 0 and t = 10.
[0455] Regarding formula (6), in each example and each comparative example, each value of Ic(t) and Is(t) within the range of 0 ≤ t ≤ 30 is a value within the range of values between t = 0 and t = 30.
[0456] Regarding formula (7), in each example and each comparative example, each value of Is(t) / I(t) within the range of 30 < t ≤ 60 is a value within the range of values between t = 30 and t = 60.
[0457] <Example 1>
[0458] <Low-temperature fixing property>
[0459] Prepare a laser printer HP LaserJet Enterprise 600M603 (Hewlett-Packard Company), from which the fixing unit is removed to evaluate the low-temperature fixing property. The removed fixing unit is modified so that the temperature can be adjusted arbitrarily and the processing speed is 440 mm / sec.
[0460] In a normal temperature and humidity environment (23.5°C, 60% RH), use this printer to produce an unfixed image with a toner loading per unit area of 0.5 mg / cm 2 . Then, pass this unfixed image through the fixing unit adjusted to 160°C or higher. Use "Plover Bond Paper" (105 g / m 2 , Fox River) as the recording medium. Rub the obtained fixed image back and forth 5 times under a load of 4.9 kPa (50 g / cm 2 ) using Silbon paper, and evaluate the reduction rate (%) of the image density after rubbing.
[0461] A: The reduction rate of the image density is less than 5.0%.
[0462] B: The reduction rate of the image density is 5.0% or more and less than 10.0%.
[0463] C: The reduction rate of the image density is 10.0% or more and less than 15.0%.
[0464] D: The reduction rate of image density is 15.0% or more
[0465] The results are shown in Table 5.
[0466] <Fog>
[0467] LaserJet Enterprise 600M603 was used. 100,000 sheets were printed out with the printer under normal temperature and humidity (23.5°C, 60% RH). Then, one sheet with an image having a white background was printed out. The reflectivity of the resulting image was measured with a reflection densitometer (reflectometer model TC-6DS, Tokyo Denshoku Co., Ltd.). A green filter was used as the filter for measurement.
[0468] Assuming Ds (%) as the minimum value of the white background reflectance and Dr (%) as the reflectance of the transfer material before image formation, Dr-Ds was taken as the fogging value and evaluated according to the following criteria.
[0469] A: Fogging less than 1%
[0470] B: Fogging is 1% or more and less than 3%
[0471] C: Fogging is 3% or more and less than 5%
[0472] D: Fogging is more than 5%
[0473] The results are shown in Table 5.
[0474] <Heat storage resistance>
[0475] 10 g of the toner was weighed into a 50 mL plastic cup and left in a thermostatic bath at 55° C. for 3 days. After leaving, the toner was visually observed and the blocking property was evaluated by the following criteria. A rating of C or higher was judged as good.
[0476] A: When the cup was rotated, the toner broke immediately.
[0477] B: Some clumps are present but become smaller and break up when the cup is rotated.
[0478] C: Even when the cup was rotated, lumps remained.
[0479] D: Large clumps which do not break up even when the cup is rotated.
[0480] The results are shown in Table 5.
[0481] <Image peeling>
[0482] Using LaserJet Enterprise 600M603, 10 images were output under low temperature and low humidity environment (15.0°C, 10% RH). A 50 mm square solid image was formed in the center of the transfer paper as an image. Under the same environment, the image was folded in the middle 20 times continuously, and the degree of image peeling of the solid image was visually evaluated.
[0483] The evaluation criteria are as follows.
[0484] A: Confirm that there is no image peeling.
[0485] B: Slight image peeling was observed at the folded portion.
[0486] C: Image peeling was observed at the folded portion, but was not a problem for practical use.
[0487] D: Image peeling was observed also in portions other than the folded portion.
[0488] The results are shown in Table 5.
[0489] <Heat-fouling resistance>
[0490] A laser printer HP LaserJet Enterprise 600M603 (Hewlett-Packard Company) was prepared in which the fixing unit was removed to evaluate the hot offset resistance. The removed fixing unit was modified so that the temperature could be arbitrarily adjusted and so that the process speed was 440 mm / sec.
[0491] Under normal temperature and humidity conditions (23.5°C, 60% RH), the printer was used to produce a toner loading of 0.5 mg / cm per unit area. 2 The unfixed image was fixed at each temperature while the set temperature was raised in increments of 5°C from an initial temperature of 100°C. The hot offset resistance was then evaluated according to the following criteria.
[0492] The low-temperature fixing starting point is the lowest temperature at which a cold offset phenomenon (part of the toner adheres to the fixing unit) is not observed.
[0493] A: The highest temperature at which hot offset does not occur is 50° C. or more higher than the temperature at the start point of low-temperature fixing.
[0494] B: The highest temperature at which hot offset does not occur is 40° C. or 45° C. higher than the temperature at the starting point of low-temperature fixing.
[0495] C: The highest temperature at which hot offset does not occur is 30° C. or 35° C. higher than the temperature at the starting point of low-temperature fixing.
[0496] D: The highest temperature at which hot offset does not occur is 25° C. or less higher than the temperature at the start point of low-temperature fixing.
[0497] The results are shown in Table 5.
[0498] <Examples 2 to 18, Comparative Examples 1 to 10>
[0499] The toners shown in Tables 4-1, 4-2, and 4-3 were evaluated as in Example 1. The results are shown in Table 5.
[0500] [Table 5]
[0501]
[0502] In the table, "C" means "Compare".
[0503] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A toner comprising toner particles containing a resin component, characterized in that: The resin component contains an amorphous polyester and a crystalline polyester, and in the measurement of the depth distribution of secondary ions on the surface of the toner particles by a time-of-flight secondary ion mass spectrometer (TOF-SIMS), assuming Ia(t) as the intensity of secondary ions derived from the amorphous polyester at a depth of t nm from the surface of the toner particles, Ic(t) as the intensity of secondary ions derived from the crystalline polyester at a depth of t nm from the surface of the toner particles, and I(t) as the total detected intensity of secondary ions derived from the resin contained in the toner particles at a depth of t nm from the surface of the toner particles, the following formulas (1) and (2) are satisfied in the range of 0 ≤ t ≤ 10: Ia(t) > Ic(t) > 0.0000 (1) (Ia(t) + Ic(t)) / I(t) ≥ 0.80 (2) and in the range of 10 < t ≤ 30, there is only one intersection point between the depth distribution curve of Ia(t) and the depth distribution curve of Ic(t), the amorphous polyester is a condensate of a dicarboxylic acid component and a diol component, the diol component contains a bisphenol A alkylene oxide adduct having an average addition mole number of alkylene oxide of 3.0 to 5.0, and the alkylene oxide is selected from ethylene oxide and propylene oxide.
2. The toner according to claim 1, wherein in the depth distribution measurement of the secondary ions on the surface of the toner particles, assuming Ic(0) as the intensity of the secondary ions derived from the crystalline polyester at t=0, and I(0) as the total detected intensity of the secondary ions derived from the resin contained in the toner particles at t=0, the following formula (3) is satisfied: 0.10≤Ic(0) / I(0)≤0.40 (3).
3. The toner according to claim 1 or 2, wherein in the depth distribution measurement of the secondary ions on the surface of the toner particles, assuming Ic(30) as the intensity of the secondary ions derived from the crystalline polyester at t=30, and I(30) as the total detected intensity of the secondary ions derived from the resin contained in the toner particles at t=30, the following formula (4) is satisfied: 0.40 <Ic(30) / I(30)≤0.90 (4)。 4. The toner according to claim 1 or 2, wherein Ic(t) satisfies the following formula (5) in the range of 0≤t≤10: 0.0100≤Ic(t)≤0.0350 (5). 5 . The toner according to claim 1 , wherein the resin component contains a styrene acrylic resin. 6 . The toner according to claim 5 , wherein a content ratio of the styrene acrylic resin in the resin component is 50% by mass to 99% by mass.
7. The toner according to claim 5, wherein in a depth distribution measurement of secondary ions on the surface of the toner particles by a time-of-flight secondary ion mass spectrometer TOF-SIMS, assuming Is(t) as the intensity of secondary ions derived from the styrene acrylic resin at a depth of t nm from the surface of the toner particles, the following formula (6) is satisfied in the range of 0≤t≤30: Ic(t)>Is(t) (6).
8. The toner according to claim 5, wherein in the measurement of the depth distribution of secondary ions on the surface of the toner particles by a time-of-flight secondary ion mass spectrometer (TOF-SIMS), assuming Is(t) as the intensity of secondary ions derived from the styrene acrylic resin at a depth of t nm from the surface of the toner particles, the following formula (7) is satisfied in the range of 30 < t ≤ 60: 0.10 ≤ Is(t) / I(t) ≤ 0.50 (7).
9. The toner according to claim 1 or 2, wherein assuming SP1 (cal / cm 3 ) 1 / 2 as the SP value of the crystalline polyester and SP2 (cal / cm 3 ) 1 / 2 as the SP value of the non-crystalline polyester, then SP2 - SP1 is 3.00 to 3.
70.
10. The toner according to claim 1 or 2, wherein the SP value (cal / cm 3 ) 1 / 2 of the non-crystalline polyester is 12.40 to 12.
90.
11. The toner according to claim 1 or 2, wherein the weight average molecular weight of the crystalline polyester is 3000 to 50000.
12. The toner according to claim 1 or 2, wherein the weight average particle diameter D4 of the toner particles is 4.00 μm to 15.00 μm.
13. The toner according to claim 1 or 2, wherein the crystalline polyester is a condensate of monomers including a linear aliphatic dicarboxylic acid and a linear aliphatic diol.
14. The toner according to claim 1 or 2, wherein the toner particles are suspension polymerization toner particles.
Citation Information
Patent Citations
Electrostatic charge image developing toner, method for producing the same, electrostatic charge image developer and image forming method
JP2011149986A
Toner for electrostatic charge image development and manufacturing method of the same, developer including toner, and image forming apparatus, image forming method, and process cartridge using the same
JP2015169770A
Toner, developing apparatus, and image-forming apparatus
CN107561883A
